GSK-J1-loaded, hyaluronic acid-decorated metal-organic frameworks for the treatment of ovarian cancer - Yang, Bing; Liu, Wenxu; Li, Meiying; Mo, Jingxin (Frontiers in Pharmacology, 2022)
Despite intensive research, ovarian cancer has the highest mortality rates among gynecological malignancies, partly because of rapid acquisition of chemoresistance for platinum therapy. Hence , Strategy for overcoming resistance to platinum is demanding in treatment of ovarian cancer. In this study, we designed hyaluronic acid-decorated metal-organic frameworks for targeted delivery of GSK-J1, a JMJD3 demethylase inhibitor, (designated as HA@MOF@GSK-J1) to synergistically treat carboplatin-resistant ovarian cancer. This HA@MOF@GSK-J1 achieved an outstanding effectiveness in the inhibition of ovarian cancer in vitro. HA@MOF@GSK-J1 demonstrated higher induction of apoptosis, reduced cell motility, and diminished cell spheroids by attenuation of HER2 activity through the effectual activation of H3K27 methylation in its promoter area. Furthermore, our in vivo results confirmed HA@MOF@GSK-J1 can sensitize resistance ovarian tumor xenografts. Our study supported HA@MOF@GSK-J1 as a targeted strategy to improve treatment of carboplatin-resistant ovarian cancer.